New training model using chickens intestine for pediatric intestinal anastomosis - Santos,Deivid Ramos dos (2019)
Abstract Purpose: To develop a new low-cost, easy-to-make and available training model using chickens’ intestine for infant intestinal anastomosis. Methods: Segments of chicken intestine were used to create an intestinal anastomosis simulator. We tried to perform an end-to-end, end-to-side and side-to-side anastomosis. Handsewn sutured anastomosis were performed in single layered with interrupted prolene 5-0 suture. The parameters analyzed were cost, intestine's diameter and length, anastomosis patency and flow-through and leakage amount. Results: In all cases it was possible to make the anastomosis in double layered without difficulties, different from the usual ones. There was a positive patency at all anastomoses after the end of the procedure, with no need for reinterventions. Conclusion: The new training model using chickens’ intestine for infant intestinal anastomosis is low-cost, easy-to-make and easy available.